Efeitos dos agentes de impregnação e coberturas comestíveis sobre a secagem e sobre a qualidade física e nutricional do abacaxi - Silva, Keila de Souza [UNESP] (2013)
In this work, we proposed to combine technologies and evaluate their influence on the drying kinetics and on nutritional characteristics and physicochemical pineapple, with the aim of improving quality of dried fruit. Pineapples cut in the shape of a trapezoid were osmotically dehydrated in ternary solution of sucrose (40 to 50%), calcium lactate (2 and 4%) and water for different times (0, 1, 2, 4 and 6 hours) at room temperature constant stirring (27°C and 1850 rpm), in order to evaluate the efficiency of the process, the water activity and changes in the composition, color and texture of the product during the process, as well as the diffusivity of the three components, water, sucrose, and calcium, on pineapple. It was observed that calcium impregnation was higher in the samples submitted at solutions with higher concentrations of sucrose and calcium lactate. Calcium addition accentuated the water loss on the product and reduced the sucrose gain, increasing the efficiency of the process and reducing the water activity of the product. Sucrose and water diffusivity decreased with calcium addition in the osmotic solution. Moreover, the diffusion coefficients of calcium increased with increasing its concentration in the solution. Neither calcium lactate addition in the solution and neither the process time changed the brightness and chromaticity of the samples. The observed changes in the color of the product were due to the increasing sucrose concentration. Despite the effective uptake of calcium in the samples, it was not possible to see an increase in firmness compared to fresh fruit. However, the process has been efficient regarding to calcium impregnation, whose content found in 100 g of pineapple treated for 6 hours in solution of sucrose added 4% of calcium lactate corresponding to 10% of the recommended daily intake. It was also investigated the uptake of calcium together with vitamin C ...